Climate change adaptation options to inform planning of agriculture and food systems in The Gambia: A systematic approach for stocktaking - Segnon, Alcade C; Zougmoré, Robert B.; Green, Rosemary; Ali, Zakari; Carr, Tony W; Houessionon, Prosper; M'boob, Sulayman; Scheelbeek, Pauline (Frontiers Media, 2022)
Identifying and assessing adaptation options are key pre-requisite steps to adaptation prioritization and effective adaptation planning. In this paper, we presented a systematic approach for adaptation stocktaking, combining a systematic mapping and an outcome-oriented and evidence-based assessment, illustrated using the case of The Gambia. This study systematically mapped 24 adaptation options that can potentially inform adaptation planning in The Gambia agriculture and food systems and assessed how the identified options contribute to the pillars of Climate-Smart Agriculture. Because of the paucity of evidence sources from The Gambia, we collated evidence from both The Gambia and the West Africa region. We found that many of the documented options, such as climate-resilient crop varieties, crop diversification, climate information use, and weather indexed-based insurance have the potential to increase agricultural productivity and income while building resilience to climate change. While several options, such as soil and water conservation practices can positively contribute to climate change mitigation, others such as manure and inorganic fertilizers can have no or negative impacts on mitigation. Agroforestry practices and System of Rice Intensification have the potential to make a triple impact. The paucity of evidence from The Gambia and the highly contextual and differential impacts of the identified adaptation options underscore the importance of careful consideration of barriers and enablers when developing and deploying policy and interventions to sustainably increase productivity and income while building resilience to climate risks and reducing GHGs emissions. Stakeholder engagement and participatory research action are crucial in selecting and testing the priority adaptation options which can maximize their potentials in specific agricultural and food system contexts, such as in The Gambia. Because of the heterogeneity in household vulnerability and socioecological circumstances, targeting options to the right contexts will also be crucial to avoid maladaptation. We highlighted key knowledge gaps in the understanding of the effectiveness and feasibility of the identified adaptation options in The Gambia. Beyond The Gambia, the approach can also be useful for and replicated in other least developed countries in the West African region, that are currently developing their National Adaptation Plan.